Effect of Freeze-Thaw Pretreatment on Extraction Yield and Antioxidant Bioactivity of Corn Carotenoids (Lutein and Zeaxanthin) - Yan Jiao; Dajing Li; Ying Chang; Yadong Xiao (Journal of Food Quality)
As a green and low-energy pretreatment method, the effect of freeze-thaw (FT) pretreatment on extraction yield and antioxidant bioactivity of carotenoids of the corn gluten meal (CGM) were evaluated in this study. The CGM particles ruptured in FT treatment due to the repeated damage caused by FT to CGM particles. The carotenoid compounds of pretreated CGM were lutein, zeaxanthin, β-carotene, and cryptoxanthin. Among them, the major carotenoids are lutein and zeaxanthin. The optimized FT pretreatment conditions included freezing temperature of −20°C, moisture content of 100%, and 2 cycles. An increase in the yield of lutein and zeaxanthin was observed in the range of 2.23–16.39 µg/g and 4.66–36.3 µg/g as a result of pretreatment as against 1.17 and 2.52 µg/g of the untreated sample, respectively. Moreover, the release of lutein and zeaxanthin from CGM was facilitated by FT pretreatment and increased the antioxidant activity of the carotenoids.